Investigation of Slow Eutectoid Element on Tensile Properties and Superplasticity of a Forged SP700 Titanium Alloy - Dong Han (MDPI AG, 2021)
The tensile properties and superplasticity of a forged SP700 alloy with slow eutectoid element (1.5%Cr) addition were investigated in the present paper. The results of the microstructures showed that slow eutectoid element Cr has a significant influence on stabilizing the β phase and the SP700Cr alloy showed a uniform duplex and completely globular microstructure after annealing at 820 °C for 1 h and aging at 500 °C for 6 h. The results of the tensile tests showed that the yield strength, ultimate tensile strength and elongation of the alloy with optimized microstructure were 1312 MPa, 1211 MPa and 10% at room temperature, and the elongation was achieved to 1127% at 770 °C. Compared with that of the SP700 alloy, the strain rate sensitivity of the SP700Cr alloy showed a higher value. The microstructures after elevated temperature tensile tests showed that the higher density of dislocations and twins exists in SP700 alloy and the lower density of dislocations favor distribution in SP700Cr alloy. Based on the above results, the tensile properties and superplasticity of the forged SP700 alloy with 1.5% Cr addition was analyzed. In addition, microstructure characteristics were investigated by the TEM and EBSD technologies.